Post living kidney donation risk in relation to the donor baseline demographic characteristics: a systematic review and meta-analysis - Bellini, MI; Nozdrin, M; Pengel, L; Knight, S; Papalois, V (Oxford University Press, 2022)
Introduction: Living kidney donation risk is likely to differ according to donor’s demographic characteristics.